EVALUASI PERTUMBUHAN MIKROALGA DALAM MEDIUM POME: VARIASI JENIS MIKROALGA, MEDIUM DAN WAKTU PENAMBAHAN NUTRIENT - Muhammad Zaini Mahdi; Yasinta Nikita Titisari; H Hadiyanto (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2012)
POME is a liquid waste produced by crude palm oil industry. POME has not been processed optimally and therefore it is problem for environment due to high level of COD and BOD. Algae is known as bioabsorbent which can neutralize pollutants components in the liquid waste. For its growth, microalgae needs nutrients containing carbon, nitrogen, and phosphor. These nutrients are required for photosynthetic to convert carbon source into biomass. POME contains large amount of C, N, P and therefore this research is aimed to study the potential of POME as medium growth of algae Spirulina, Nannochloropsis, and Chlorella. The experiment was done by performing variation of nutrients, type of water, and time of nutrient feeding. The nutrients were urea and sodium bicarbonate. The steps of experiment were preparing the medium, cultivating the microalgae, observing biomass, counting the algae cells, and making calibration curve. The results showed that the best medium for microalgae is POME, Spirulina could grow better in the POME medium than Chlorella and Nannochloropsis, and nutrients added every 2 days was better than adding nutrients in the beginning and without addition of nutrients.